2021
DOI: 10.18502/cmm.6.4.5332
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the fungicidal efficacy of photodynamic therapy with methylene blue, silver nanoparticle, and their conjugation on oral Candida isolates using cell viability assay

Abstract: Background and Purpose: This study aimed to evaluate the effect of common photodynamic therapy and photodynamic therapy by the silver nanoparticle, methylene blue, and their combination on biofilm and plankton cells of standard oral Candida isolates using cell viability assay. Materials and Methods: In this in vitro study, biofilm and plankton cells of Candida species(i.e. C .albicans and C. parapsilosis) and plankton cells of Candida glabrata were treated with methylene blue, silver nanoparticle, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…In different types of infections, it has been shown that photodynamic therapy is strain- and photosensitizer-dependent [ 56 ] and that it has a cumulative effect with the mixture of other antimicrobials [ 57 ]. A factor that must be taken into account and that can increase the antimicrobial activity of the photosensitizer is the incubation/pre-irradiation time, since this could increase the joint effect of the MB + LED [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In different types of infections, it has been shown that photodynamic therapy is strain- and photosensitizer-dependent [ 56 ] and that it has a cumulative effect with the mixture of other antimicrobials [ 57 ]. A factor that must be taken into account and that can increase the antimicrobial activity of the photosensitizer is the incubation/pre-irradiation time, since this could increase the joint effect of the MB + LED [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result differed from the findings of the present study, in which a greater amount of energy was applied -12.6 J provided by a dose of 450 J/cm 2 eliminating 76.73% of C. albicans and 65.02% of C. non-albicans. Lavaee et al [42] showed that aPDT using methylene blue as photosensitizer (1.92 J/cm 2 for 60 seconds) showed an antifungal effect only on C. albicans. Combination of methylene blue and silver nanoparticles did not have any effect on C. albicans, but did on C. glabrata and C. parapsilosis concluding the effect of aPDT was strain and photosensitizer dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies in the literature sought to evaluate the action of PSs associated with metallic NPs, such as AgNPs, on fungal inactivation. [46][47][48][49] Maliszewska et al 50 For PDI studies, only the concentration of 7 mg/L of PCs was used. The authors found that there were no great effects when NPs were applied alone.…”
Section: Photoinactivation Of Candida Albicansmentioning
confidence: 99%